An Accounting Study of the Bhubuwan Tradition - Syarifa, Hafidha Raniz; Riharjo, Ikhsan Budi; Fidiana, Fidiana (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Accounting has evolved beyond formal systems into social practices embedded in cultural and relational contexts. One example is the bhubuwân tradition in the Madurese community, a gift-giving practice in ceremonial events that involves structured economic mechanisms and record-keeping. However, this practice has rarely been examined from a contextual accounting perspective. Therefore, this study aims to examine accounting practices within the bhubuwân tradition using a contextual approach. This study employs a qualitative ethnographic method conducted in Jaddih Village, Bangkalan Regency. Data were collected through interviews, participant observation, and documentation, and analyzed using an ethnographic model to capture the meanings and practices developed within the community. The results show that bhubuwân embodies informal accounting functions, including recording, measurement, control, and accountability, which are documented in the ongghâân book. These practices operate through social mechanisms based on trust, norms, and reciprocity, supported by an organized social structure. Furthermore, bhubuwân has multidimensional meanings, functioning as social debt and credit, a collective funding mechanism, a form of contribution, and a long-term social investment. This study concludes that accounting in a cultural context functions not only as an economic tool but also as a social mechanism that maintains balance, justice, and the sustainability of social relationships within the community.